Seasonal changes of some physical and chemical parameters of water in the Turag river, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2025)
The study was carried out to determine the water quality of Turag River in Dhaka city and its seasonal variations due to changes in physico-chemical parameters throughout the post-monsoon, pre-monsoon and monsoon seasons from October 2020 to September 2021. Samples were collected in three separate seasons to evaluate different physical and chemical parameters of the water, such as temperature, water depth, transparency, pH, DO, alkalinity, hardness, etc., using established procedures. In all seasons, the pH and temperature levels of river water were within the standard limit. Water transparency exceeded the standard level during the pre-monsoon and monsoon seasons, but was below the permissible limit after the monsoon. The lowest concentration of dissolved oxygen (DO) and the highest concentration of free CO2 were observed in all seasons, which seriously harmed aquatic organisms and destroyed their habitat in the river. The alkalinity of the Turag River exceeded the regulatory standard throughout each season. Total hardness levels exceeded the acceptable range in all seasons and water samples were classified as very hard. Positive and negative correlations were found in some water parameters. The comparative study showed that the environmental condition of the Turag River was significantly degraded due to the presence of a significant amount of pollutants released by Dhaka city. Therefore, effective measures should be taken to reduce the pollution level and alleviate the existing aquatic environmental problems in the Turag River.Bangladesh J. Zool. 52(3): 209-223, 2024